1980
DOI: 10.1177/002246698001400307
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic/Instructional Link in Individualized Education Programs

Abstract: Enactment of P.L. 94-142 has provided a major impetus to the provision of a free and appropriate education to all handicapped children. A major provision in P.L. 94-142 is the requirement that all handicapped children receiving special education be provided with an Individualized Education Program (IEP). The IEP, therefore, is to incorporate special education, which is defined as "specially designed instruction." Literature pertaining to IEP development states that instruction must be linked to assessment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 2 publications
2
15
0
3
Order By: Relevance
“…Unfortunately, research has shown that the student assessment data and the instructional goals often have low correspondence (e.g., Fiedler & Knight, 1986;Schenck, 1980;Smith & Simpson, 1989). In addition, the data suggest that errors in developing educational materials and activities are in both directions-too difficult and too easy.…”
Section: Task Difficultymentioning
confidence: 99%
“…Unfortunately, research has shown that the student assessment data and the instructional goals often have low correspondence (e.g., Fiedler & Knight, 1986;Schenck, 1980;Smith & Simpson, 1989). In addition, the data suggest that errors in developing educational materials and activities are in both directions-too difficult and too easy.…”
Section: Task Difficultymentioning
confidence: 99%
“…Zo blijken adviezen die betrekking hebben op de opvang in het speciaal onderwijs tamelijk willekeurig aan diagnoses te zijn gekoppeld (Schenck, 1980;Frame, Clarizio, Porter & Visonhaler, 1982). De adviezen lopen meestal sterk uiteen bij dezelfde diagnose en zijn bovendien weinig specifiek en concreet.…”
Section: Bevordering Van Behandelingsgerichtheidunclassified
“…The discussion so far gives us reason to believe that translating assessment data into decisions on goals, objectives, methods, learning activities, etc., is problematic (see also Schenck, 1980). One of the premises behind the IEP is that it is possible to link diagnosis and instruction.…”
Section: The Diagnostic/instructional Linkmentioning
confidence: 99%
“…These data are used to make a reliable and valid placement decision. By referring students to special education we expect special education to offer the admitted students an appropriate education (Schenck, 1980). The special education team has to consider seriously the handicaps, learning and social problems, abilities, etc.…”
Section: Introductionmentioning
confidence: 99%